(untitled) (Journal of Asian Development Studies, 2025)
The research examines how Pre-arrest Bail Applications and Post-arrest Bail Applications and Writ Petitions function as separate legal genres in the Pakistani legal system while investigating their forensic and applied linguistic characteristics. The main goal examines how the rhetorical moves function together with narrative elements and distinct legal conventions throughout these legal documents. For the evaluation researchers chose a qualitative methodology that included purposive sampling and manual pattern recognition in legal discourse. The research utilizes Bhatia’s (1993) Genre Analysis Framework to study 12 legal documents which include four documents from each category retrieved from official digital archives of Peshawar High Court and Lahore High Court. All three legal subgenres contain typical features of legalese yet each has its own particular structural sequence of moves that supports their unique communication task. Writ petitions usually contain wider constitutional arguments but bail applications focus on individual liberties together with evidence from the specific case. The reported data demonstrates the struggles facing ordinary people to grasp legal terminology because it shows the value of straightforward language in judicial proceedings. This investigation expands the forensic linguistic field while giving genre perspectives to Pakistani legal writing and promoting joint work between linguistic scholars and legal profession members. Forensic linguistic analysis benefits from regional acceptance because it uses local judicial procedures and public legal records to establish its academic foundation in Pakistani university discourse.